Praktik Pesanan Paket Aqiqah dalam Tinjauan Hukum Islam - Yasmine, Heydi Tiara (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
The research entitled The Practice of Ordering Aqiqah Packages in a Review of Islamic Law was written to answer problems related to how the practice of ordering aqiqah package products at Istiqomah Aqiqah Sidoarjo and how to review Islamic law on the practice of ordering aqiqah package products at Istiqomah Aqiqah Sidoarjo. The research data were collected by observation, interview, and literature study techniques which were then analyzed using descriptive techniques in describing ordering aqiqah packages using a greeting contract. The results of this study conclude that the practice of ordering aqiqah package products at Istiqomah Aqiqah uses a salam contract between the ordering party and Istiqomah Aqiqah where payment is made at the beginning of the contract in cash or a down payment of 30%, and delivery of the aqiqah package is submitted at the end of the agreement in the assembly contract. Even though the Istiqomah Aqiqah party has provided payment relief using a down payment of 30% in ordering the aqiqah package, it does not rule out the possibility of a delay in paying the aqiqah package and causing one party to feel disadvantaged, namely the Istiqomah Aqiqah party. Delaying the payment of the aqiqah package made by the ordering party to Istiqomah Aqiqah after it is due according to Islamic law is permissible or mubah because the pillars and conditions in ordering the aqiqah package using the salam contract have been fulfilled. And because of the willingness of the Istiqomah Aqiqah parties to postpone the payment of the aqiqah package, this cannot be avoided due to unexpected things.